Pemberian Pupuk Anorganik dan Air Pada Tanah Gambut Terhadap Pertumbuhan Kelapa Sawit di Pre-Nursery - , Gusmawartati; , Wardati (Jurnal Agro Teknologi Tropika, 2012)
The objective of this research was to study the optimal waters requirement of palm oil seedling at pre-nursery peatsoil which is applied with in-organic fertilizer to enhance growth of oil palm on pre-nursery in peat soil. The research hasconducted on peat soil growth media, taken from Desa Rimbo Panjang Kab. Kampar, Province of Riau. The experimentalunits were arranged in Factorial Completely Randomized Design with three replications. The first factor is: 0, 1â2 and 1times of recommended dosage. The second factor is: 2, 3 and 4 (times/day) of watering. Parameters studied were anincrease seedling height, number of leaves and stem diameter. The results showed that application of in-organic fertilizerwith 1 time of recommended dosage in 2 times of watering/day in trended to give the best growth of oil palm seedlings,which was equal to growth standard recommended by the Indonesian Palm Oil Research Center.